2014
DOI: 10.1063/1.4905110
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent transport characteristics of graphene/n-Si diodes

Abstract: Realizing an optimal Schottky interface of graphene on Si is challenging, as the electrical transport strongly depends on the graphene quality and the fabrication processes. Such interfaces are of increasing research interest for integration in diverse electronic devices as they are thermally and chemically stable in all environments, unlike standard metal/semiconductor interfaces. We fabricate such interfaces with n-type Si at ambient conditions and find their electrical characteristics to be highly rectifyin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 18 publications
10
34
0
Order By: Relevance
“…of ) with forward bias, meaning that the application of a forward bias homogenize the barrier fluctuations. The value of ~74 at zero bias is in agreement or below what has been reported for planar Gr/semiconductor heterojunctions 44,46,49 . This lead to the remarkable result that the tip-geometry and the transfer process do not introduce extra-inhomogeneity.…”
Section: Fig 3csupporting
confidence: 89%
“…of ) with forward bias, meaning that the application of a forward bias homogenize the barrier fluctuations. The value of ~74 at zero bias is in agreement or below what has been reported for planar Gr/semiconductor heterojunctions 44,46,49 . This lead to the remarkable result that the tip-geometry and the transfer process do not introduce extra-inhomogeneity.…”
Section: Fig 3csupporting
confidence: 89%
“…Similar values have been reported for graphene junctions with other standard semiconductors. [ 12,13,34,35 ] The I sat values are then extracted from the same fi t by Equation ( 2) as the extrapolated current at V DS = 0 (from Figure 3 d, I sat = 2.6 × 10 −11 A for graphene/C 60 /Al diode), and are used afterwards for the energy barrier extraction.…”
Section: Resultsmentioning
confidence: 99%
“…. To explain the temperature dependence of B  , S. Kim et al [152] suggested the barrier inhomogeneity model [47] [54][153]- [154], which considers a Gaussian distribution of the barrier heights around a mean value BM  and with standard deviation σ:…”
Section: Experimental Aspects Of the Graphene/semiconductor Junctionmentioning
confidence: 99%